PERLINDUNGAN HUKUM KONSUMEN DALAM LAYANAN PAYLATER DAN PINJAMAN ONLINE DI INDONESIA - Kurniawan, Rahmad Ready; Faisol, Faisol (Gapenas Publisher, 2025)
This study aims to analyze the forms of legal protection for consumers in services.Buy Now Pay Later (PayLater) and online lending in Indonesia. The primary focus is to identify how existing regulations, such as the Financial Services Authority Regulation (POJK) and the Personal Data Protection Law, can protect consumers from abusive practices, hidden fees, and the risk of default, and how on-the-ground practices reflect the implementation of these regulations. This study employs a normative juridical method with a conceptual and comparative regulatory approach, supported by qualitative descriptive analysis of secondary data. Data were collected through a review of the latest regulations (POJK No. 10/2022, POJK No. 22/2023, Law No. 27/2022), official OJK reports (SLIK Statistics, APPK, PASTI Task Force), and industry survey results. Research shows that PayLater and online lending services are growing rapidly in Indonesia, driven by the consumer behavior of the younger generation. OJK regulations have provided a protective framework, but their effectiveness is limited to legitimate providers, while misuse of personal data, hidden fees, and aggressive collection practices remain significant issues. This research only uses secondary data from public reports, regulations, and academic literature. This study contributes to the development of legal science and consumer protection by highlighting the urgency of strengthening regulations. The results of this study are useful for regulators (OJK, Kominfo), fintech industry players, academics, and policy makers in formulating more effective consumer protection strategies in the digital financial services sector.